Penggunaan Pin ADC (Analog to Digital Converter) pada Mikrokontroler ATmega8535 untuk Menghasilkan Catu Daya Digital - Pauzan, Muh; Yanti, Indri (Faculty of Engineering, Universitas Tanjungpura, 2019)
Digital power supply with LM317 regulator have been built. The output voltage of LM317 regulator is digitalized by means of ADC pins in ATmega8535 microcontroller. 128 prescaler is used to make the microcontroller’s frequency in the region of ADC’s frequency, therefore ADPS0, ADPS1 and ADPS2 must be high (1). AVcc (5V) is used as voltage reference, it is means that REFS0, REFS1 is set to high (1) and low(0) respectively. LCD 16x2 is used to display the voltage output of LM317. The research divided into three stages: theoretical study, simulation and implementation. Theoretical study consists of AC-DC conversion and digitalizing the output voltage of LM317. Aim of the study of AC-DC conversion is to know the specification of elements to build 30 V, 1 A power supply. Circuits and coding in ATmgea8535 for converting analog to digital is studied. Proteus software is used for designing the circuits and simulation while Atmel Studio for compiling the coding. The difference of voltage measurements is found between digital voltmeter and LCD in the implementation stage, the range is 0.2-3.19 V. After callibration, same voltage values both on voltmeter and LCD is displayed. It is concluded that minimum-maximum output voltage of power supply is 1.2-27.10 V.